Indigenous and divergent voices in the business school: Who’s listening? - Peredo, Ana (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
There are increased efforts on the part of business schools to recruit more Indigenous students and faculty members in response to the call for greater inclusivity. Nevertheless, an inhospitable climate for Indigenous who wish to retain their cultural identity remains a challenge. This article describes the experience of a faculty member from a “recognizable minority” recruited to give an “inclusive” face to a business schools conventional models, and outlines the unwelcoming atmosphere faced by racialized students and faculty members in institutions that at the same time try to mould them into mainstream models. Can business schools allow Indigenous and other divergent voices to challenge and even reform mainstream models?